PENGARUH STRATEGI BERSAING TERHADAP TINGKAT VOLUME PENJUALAN SPAREPART PADA PT.MORITA TJOKRO GEARINDO DI JAKARTA - Akbar, Muhamad; Nadia, Ahsanu (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to see the effect of Competitive Strategy on the Sales Volume Level of Car Parts at PT. Morita Tjokro Gearindo in Jakarta. The population in this study were all consumers of PT. Morita Tjokro Gearindo with a total sample of 90 respondents, with the sampling technique using incidental sampling techniques. The respondent data technique used was a questionnaire (questionnaire) for each respondent who was given 18 statements. Then the data obtained were analyzed using the validity test, reliability test, linear regression analysis, t test, and analysis of the coefficient of determination (R2). Based on the research results of the coefficient of determination (r square) of 0.172, which means that the Competitive Strategy variable has a significant positive result on the Increase in Sales as evidenced by the t - test 3,868 > t - table 1,662, it means that H0 is rejected, and H1 is accepted. So it can be revealed that there is a significant and positive influence between competitive strategy on sales volume level.